2013
DOI: 10.4018/978-1-4666-1987-6.ch005
|View full text |Cite
|
Sign up to set email alerts
|

Playability Design Patterns

Abstract: Learning through play is currently an effective and attractive educational strategy. Recently, many educational video games have failed because methods of analysis have not been used to discuss playability level in a structured way. Ensuring a good player experience characterized by playability requires cooperation and collaboration between game designers and educators. To this end, the authors have proposed a new set of patterns to support educational video game design and analysis. These patterns aim to faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…EVGs have proved to be very popular due to the fact that they teach, build and strengthen certain skills and concepts while being enjoyable. During our research we found many EVGs that appeared on the market before their efficacy had been ensured (González Sánchez et al, 2009;Ibrahim et al, 2011Ibrahim et al, , 2012a, as a result, numerous games have failed, due to the failure of designers to achieve the player objectives in a fun and attractive learning environment, and due to the lack of standards that connect educational and playful contents in an integrated environment (De Freitas, 2006;Kelle et al, 2011). Also, Royle (2008) related the failure of some EVGs to the lack of motivation and educational content "Such efforts have failed either because games designed to educate do not engage their intended audience, or because truly engaging games do not provide enough educational value."…”
Section: Introductionmentioning
confidence: 91%
“…EVGs have proved to be very popular due to the fact that they teach, build and strengthen certain skills and concepts while being enjoyable. During our research we found many EVGs that appeared on the market before their efficacy had been ensured (González Sánchez et al, 2009;Ibrahim et al, 2011Ibrahim et al, , 2012a, as a result, numerous games have failed, due to the failure of designers to achieve the player objectives in a fun and attractive learning environment, and due to the lack of standards that connect educational and playful contents in an integrated environment (De Freitas, 2006;Kelle et al, 2011). Also, Royle (2008) related the failure of some EVGs to the lack of motivation and educational content "Such efforts have failed either because games designed to educate do not engage their intended audience, or because truly engaging games do not provide enough educational value."…”
Section: Introductionmentioning
confidence: 91%
“…In general terms, "playability" [6] can be defined as: "a set of properties that describe the player experience using a specific game system whose main objective is to provide enjoyment and entertainment when the player plays alone or in company". In extension, the educational playability is not limited to playful objectives but must take into account educational objectives, such as learning while having fun, improving the abilities of students to solve complex problems, reinforcing players' skills and improving player experience [7] (Table 1). Table 1.…”
Section: What Can We Learn From Video Games?mentioning
confidence: 99%